Thin-film microbattery fabrication by PLD: a comprehensive mini-review - Curcio, Mariangela; Teghil, Roberto; De Bonis, Angela (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
This mini-review reports the latest results on Pulsed Laser Deposition (PLD) for the design and development of microbatteries. Advances in the deposition of thin films for cathodes, anodes and electrolytes are considered separately, the focus being on studies reporting the electrochemical characterization and performance of electroactive films. Some results on the positive effects of coatings to study and mitigate anode degradation are also discussed.